Analisis Proses Pembelajaran Dalam Jaringan (Daring) Di Masa Pandemi Covid-19 Pada Mahasiswa - Alfania Salsabilla; Cloudia Yolanda; Destrya Darma Putri; Heriyanto Heriyanto; Tasya Adinda Putri; Jeni Wardi (Universitas Lancang Kuning, 2021)
This research intends to gather objective data on online learning activities for students at Lancang Kuning University's Faculty of Economics, based on the policy of studying at home during the COVID-19 emergency response period. The descriptive research method was applied in the form of survey research. The data was collected via indirect communication tactics and data gathering platforms, such as the distribution of surveys using Google Forms. The participants in this study were 100 students from two majors at Lancang Kuning University's Faculty of Economics. Students' online learning activities during the COVID-19 emergency reaction period on the policy of studying at home are